Increased expression of interleukin-17 is associated with macrophages in chronic immune thrombocytopenia - Okamoto, Naoko (Int J Clin Exp Pathol, 2018)
Objectives: Interleukin-(IL-)17-mediated cells contribute to the imbalance of cellular immunity in the pathogenesis of immune thrombocytopenia (ITP). We examined samples of bone marrow (BM) clots to determine if IL-17-mediated immunological changes involve the BM and to identify clinical predictors of treatment response. Methods: We enrolled 33 patients with chronic ITP. BM clots were obtained before treatment and stained with the following markers: CD3, CD4, CD8, CD20, CD25, CD68, CD163, and IL-17. Pathological findings and clinical information, including laboratory data, were compared between the patients and 11 control subjects and between IL-17-high and -low-expression groups. Results: Univariate analysis revealed increased cells expressing CD68, CD163, and IL-17 in the patients with ITP than in the control subjects (P = 0.02, 0.001, and 0.001, respectively). The expression of both CD68 and CD163 showed correlation with IL-17 expression (r = 0.60 and 0.48, respectively). Responses to Eltrombopag were better in the IL-17-low-expression group than in the IL-17-high-expression group (P = 0.056). Conclusions: Macrophages and monocytes were associated with IL-17 expression in patients with ITP. We demonstrated that ITP is associated with IL-17-expressing monocytes/macrophages and might be more difficult to treat.